2022
DOI: 10.1038/s41598-022-05478-3
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine reduces GlyT1 expression by potentiating the p-AMPKα/BDNF signalling pathway in spinal astrocytes of rats

Abstract: Bupivacaine, a local anaesthetic, is widely applied in the epidural or subarachnoid space to clinically manage acute and chronic pain. However, the underlying mechanisms are complex and unclear. Glycine transporter 1 (GlyT1) in the spinal cord plays a critical role in various pathologic pain conditions. Therefore, we sought to determine whether bupivacaine exerts its analgesic effect by regulating GlyT1 expression and to determine the underlying mechanisms of regulation. Primary astrocytes prepared from the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Newer studies suggest that GlyT1 is also downregulated in cultured astrocytes by the activation of the protein kinase AMPK in a most likely BDNF-dependent pathway [ 83 ]. In addition to these signaling pathways that regulate the expression of GlyT1 in the plasma membrane, it was shown that there is also a microRNA- (miR) dependent mechanism that regulates the translation of GlyT1 mRNA and thereby, indirectly, the number of GlyT1 molecules within the plasma membrane [ 84 ].…”
Section: Regulation Of the Transport Activitymentioning
confidence: 99%
“…Newer studies suggest that GlyT1 is also downregulated in cultured astrocytes by the activation of the protein kinase AMPK in a most likely BDNF-dependent pathway [ 83 ]. In addition to these signaling pathways that regulate the expression of GlyT1 in the plasma membrane, it was shown that there is also a microRNA- (miR) dependent mechanism that regulates the translation of GlyT1 mRNA and thereby, indirectly, the number of GlyT1 molecules within the plasma membrane [ 84 ].…”
Section: Regulation Of the Transport Activitymentioning
confidence: 99%
“…However, there are still similarities in the regulatory effect of GlyT1 on neuronal synapses and apoptosis. The Glycine transporter protein 1 (GlyT1) inhibitor SSR504734 and the PDE4 inhibitor crotlipram improve hippocampal synaptic plasticity by increasing glycine concentrations in synapses near NMDA receptors [71].Lu et al [72]demonstrated that GlyT1 inhibition not only increases glycine concentrations in synaptic gaps but also decreases the expression of N-methyl-D-aspartate receptors (NMDARs) in synapses, thereby ameliorating neuropathic pain. In addition, persistently increased glycine concentrations near NMDARs may lead to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that NR4A1 knockdown improves cardiac function [67,71,72]. AMPK is a crucial regulator of fatty acid metabolism that can promote FFA β-oxidation by activating and improving the transcriptional activity of PPAR-α and the phosphorylation of PGC1-α[73,74]. p-AMPK can regulate lipid metabolism through multiple pathways, including increasing fatty acid intake by promoting CD36 and LPL transport[75].…”
mentioning
confidence: 99%